If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = (3 + x) + 3(2) Remove parenthesis around (3 + x) 2 = 3 + x + 3(2) Multiply 3 * 2 2 = 3 + x + 6 Reorder the terms: 2 = 3 + 6 + x Combine like terms: 3 + 6 = 9 2 = 9 + x Solving 2 = 9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + -1x = 9 + x + -1x Combine like terms: x + -1x = 0 2 + -1x = 9 + 0 2 + -1x = 9 Add '-2' to each side of the equation. 2 + -2 + -1x = 9 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 9 + -2 -1x = 9 + -2 Combine like terms: 9 + -2 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7
| x^(-1/5)=(1/3) | | x^-1/5=1/3 | | 8x+41y+10=180 | | 2n/3=4 | | x-x+3x+x+30+28=40 | | 5h-7-3h=2(h-14) | | a^3-64= | | (2c+1)=(c-5) | | 4x^2+4y^2-16x+32y-20=0 | | (2c-1)=(c-5) | | 12y-18/2 | | 16x-3=68+13+4x | | 2x+4x+2x+1+5x-6=60 | | r/s=25 | | 9x+1=9(1)+2 | | (37b-8)-9(4b+4)=-2 | | 96.8639/883.3525= | | 1-0.4p=2 | | 3x-6=-7x-6 | | 1x+16+56=90 | | (7+y)(5y+3)= | | 11x+35+35=180 | | 3p-42=31 | | 1-0.4=2 | | 18x-4+4x=172 | | 8w+12-6w=5(w+3)-2w | | a^2-16a+63=0 | | .5x+4=-6 | | -1+4/25=-1 | | 4x*2c-4+4c=0 | | t(p)=(ln(p/25))/.12 | | 2z+8-9=-30.5 |